Ներքաղաքական իրավիճակը Եգիպտոսում (1879-1882թթ.) և Օրաբի փաշայի ապստամբության նշանակությունն ու անհաջողության պատճառները - Խաչիկ Ազիզյան (ՀՀ ԳԱԱ հրատ.)
Эта статья посвящена внутриполитической ситуации в Египте во второй половине XIX века, в частности изучению деятельности и военных действий двух политических оппонентов: про-европейских сил и националистов Египта. This article is concerned with the internal political situation in Egypt in the second half of the XIX century, particularly with the study of the activities and military actions of its two opposing political powers— the subjects of the European countries and the nationalists.
Keywords: Modern History; Political Science